Teachers’ Perceived Ethical Roles in Educating Students with ASD: A phenomenological Study - Tawagen, Jane I; Pedro, Florenda L; Samson, Sheela G; Dulnuan, Joyce Ann C; Liswid, Sheryll S; Daganos, Juliane Louisse L; Agpay, Renila V; Ignacio, Teresita D (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
Equitable, and quality education of all learners worldwide are the advocates of United Nations Educational, Scientific, and Cultural Organization (UNESCO) together with Sustainable Development Goal 4 (SGD 4). Nevertheless, this devotion presents both ethical and practical challenges in the administration of inclusive practices, specifically for teachers teaching learners with Autism Spectrum Disorder (ASD). There is limited research on how Filipino teachers personally experience and make ethical decisions in inclusive classrooms for learners with ASD, particularly using a phenomenological approach in resource-limited and culturally specific contexts. The primary aim of this study is to explore the lived experience of teachers in the province of Benguet regarding their perceived ethical roles when educating learners with mild to moderate ASD in the inclusive classroom settings. Data were collected with an in-depth semi structured interview and analyzed through the lens of Colaizzi’s (1978) method. The data gathered from the study revealed that teachers demonstrated a deep commitment to their learners, as reflected in the emerged themes, encapsulated in the acronym AGAPe. AGAPe stands for: Associated Emotions within Ethical Dilemmas, Guideposts in Decision-making, Approaches and Strategies in Navigating Ethical Dilemmas, and Personal Growth. Implications suggest that respondents encountered ethical dilemmas arising from conflicts between institutional policies, administrative directives, professional boundaries, and personal values. Furthermore, emotional demands, limited training, and the need to balance individual and collective welfare within the classroom are the factors of ethical dilemma.